Epidemiology and characteristics of urinary tract infections in children and adolescents - Hanna-Wakim, Rima H.; Ghanem, Soha T.; El Helou, Mona W.; Khafaja, Sarah A.; Shaker, Rouba A.; Hassan, Sara A.; Saad, Randa K.; Hedari, Carine P.; Khinkarly, Rima W.; Hajar, Farah M.; Bakhash, Marwan; El Karah, Dima; et al. (Frontiers in Cellular and Infection Microbiology, 2015)
Background: Urinary tract infections (UTIs) are among the most common infections in the pediatric population. Over the last two decades, antibiotic resistance is increasing significantly as extended spectrum beta lactamase (ESBL) producing organisms are emerging. The aim of this study is to provide a comprehensive view of the epidemiologic characteristics of UTIs in hospitalized children, examine the risk factors of UTIs caused by ESBL-producing organisms, and determine the resistance patterns in the isolated organisms over the last 10 years. Methods: Retrospective chart review was conducted at two Lebanese medical centers. Subjects were identified by looking at the following ICD-9 discharge codes: “Urinary tract infection,” “UTI,” “Cystitis,” and/or “Pyelonephritis.” Children less than 18 years of age admitted for UTI between January 1st, 2001 and December 31st, 2011 were included. Cases whose urine culture result did not meet our definition for UTI were excluded. Chi-square, Fisher's exact test, and multivariate logistic regression were used to determine risk factors for ESBL. Linear regression analysis was used to determine resistance patterns. Results: The study included 675 cases with a median age of 16 months and female predominance of 77.7% (525 cases). Of the 584 cases caused by Escherichia coli or Klebsiella spp, 91 cases (15.5%) were found to be ESBL-producing organisms. Vesico-ureteral reflux and previous antibiotics use were found to be independent risk factors for ESBL-producing E. coli and Klebsiella spp. (p < 0.05). A significant linear increase in resistance to all generations of Cephalosporins (r2 = 0.442) and Fluoroquinolones (r2 = 0.698) was found. Conclusion: The recognition of risk factors for infection with ESBL-producing organisms and the observation of increasing overall resistance to antibiotics warrant further studies that might probably lead to new recommendations to guide management of UTIs and antibiotic use in children and adolescents.